2018
DOI: 10.1021/acs.chemmater.8b03079
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Light-Emitting Diodes Based on Formamidinium Lead Bromide Nanocrystals and Solution Processed Transport Layers

Abstract: Perovskite nanocrystal light-emitting diodes (LEDs) employing architecture comprising a ZnO nanoparticles electrontransport layer and a conjugated polymer hole-transport layer have been fabricated. The obtained LEDs demonstrate a maximum externalquantum-efficiency of 6.04%, luminance of 12998 Cd/m 2 and stable electroluminescence at 519 nm. Importantly, such high efficiency and brightness have been achieved by employing solution processed transport layers, formamidinium lead bromide nanocrystals (CH(NH2)2PbBr3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Although the PLQY of PNCs using MeOAc and EtOAc is <70% (Figure 1B), these antisolvents are commonly chosen for a higher PNC product yield to facilitate their applications, especially in LEDs [55,56]. However, Konstantatos and coworkers [57] proposed a facile route to enhance the photophysical properties of FAPbBr 3 PNCs synthesized with short-chain capping ligands such as OctA and octanoic acid: simultaneous addition of OA and PbBr 2 to the redispersed material in toluene, prior to purification with MeOAc. The presence of OA removes the presence of PNC aggregates, while PbBr 2 provides an excess of Br − anions to passivate the halide defects and strengthen the ligand binding in the PNC surface [57,58].…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PLQY of PNCs using MeOAc and EtOAc is <70% (Figure 1B), these antisolvents are commonly chosen for a higher PNC product yield to facilitate their applications, especially in LEDs [55,56]. However, Konstantatos and coworkers [57] proposed a facile route to enhance the photophysical properties of FAPbBr 3 PNCs synthesized with short-chain capping ligands such as OctA and octanoic acid: simultaneous addition of OA and PbBr 2 to the redispersed material in toluene, prior to purification with MeOAc. The presence of OA removes the presence of PNC aggregates, while PbBr 2 provides an excess of Br − anions to passivate the halide defects and strengthen the ligand binding in the PNC surface [57,58].…”
Section: Glossarymentioning
confidence: 99%
“…However, Konstantatos and coworkers [57] proposed a facile route to enhance the photophysical properties of FAPbBr 3 PNCs synthesized with short-chain capping ligands such as OctA and octanoic acid: simultaneous addition of OA and PbBr 2 to the redispersed material in toluene, prior to purification with MeOAc. The presence of OA removes the presence of PNC aggregates, while PbBr 2 provides an excess of Br − anions to passivate the halide defects and strengthen the ligand binding in the PNC surface [57,58]. This procedure affords purified FAPbBr 3 PNCs with PL peak emission at 511 nm, FWHM = 22 nm, and PLQY around 90 ± 9% (Figure 1C).…”
Section: Glossarymentioning
confidence: 99%
“…The remarkable enhancement of QDs could be attributed to complete passivation of the QDs surface states by the formation of Al-O bond network during the reactions between TMA and carboxylate/amino groups of the ligands (Fig. 2(b)) 75,91 . It was likely that the formed alumina on the surface successfully passivated the surface shallow defects, thereby enhancing the photoluminescence yield 103 .…”
Section: (Iii) and (Iv)mentioning
confidence: 99%
“…After ALD trimethylaluminium (TMA) treatment, the PL intensity can be well kept, which implies that the stability tolerance of PNC to organic polar solvents was enhanced . It is proposed that the continuous TMA pulses applied to treat PNC thin films produce a crosslinking structure to defend the solvent erosion . Interestingly, other works showed that additional water pulses could suppress the PL decay of the PNC films .…”
mentioning
confidence: 99%
“…As a self‐limitation gas‐phase surface chemical reaction, atomic layer deposition (ALD) can provide conformal and atomic‐level‐controlled thin‐film coating to keep PNC layers from the other solvents’ corrosion . After ALD trimethylaluminium (TMA) treatment, the PL intensity can be well kept, which implies that the stability tolerance of PNC to organic polar solvents was enhanced . It is proposed that the continuous TMA pulses applied to treat PNC thin films produce a crosslinking structure to defend the solvent erosion .…”
mentioning
confidence: 99%